Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1023/b:joyo.0000025323.94929.d9
|View full text |Cite
|
Sign up to set email alerts
|

Narcissistic Features in Young Adolescents: Relations to Aggression and Internalizing Symptoms

Abstract: Recent research and theory suggest narcissistic features contribute to aggression in adults. The present study examined the association of narcissistic features with aggression and internalizing symptoms in 233 students of 5th-8th grade at three inner-city schools. A factor analysis of the Narcissistic Personality Inventory in this sample revealed three factors: Adaptive Narcissism, Exploitativeness, and Exhibitionism. Regression analyses were used to predict the association of these three narcissistic feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
124
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(145 citation statements)
references
References 70 publications
15
124
2
4
Order By: Relevance
“…Of importance, it has been suggested that not all components of narcissism are inherently maladaptive or predictive of aggression; rather, certain features of the construct may work to facilitate positive outcomes such as autonomy, individuation, and self-reliance in adolescents as they navigate their transition into adulthood (Stolorow, 1986). Empirical findings have generally supported this claim, showing that only the maladaptive features of narcissism (e.g., entitlement, exploitativeness) are associated with aggression and conduct problems, whereas those features considered to be more adaptive (e.g., authority, self-sufficiency) are unrelated to these types of outcomes (Barry et al, 2003;Washburn et al, 2004).…”
Section: Juvenile Narcissismmentioning
confidence: 92%
See 4 more Smart Citations
“…Of importance, it has been suggested that not all components of narcissism are inherently maladaptive or predictive of aggression; rather, certain features of the construct may work to facilitate positive outcomes such as autonomy, individuation, and self-reliance in adolescents as they navigate their transition into adulthood (Stolorow, 1986). Empirical findings have generally supported this claim, showing that only the maladaptive features of narcissism (e.g., entitlement, exploitativeness) are associated with aggression and conduct problems, whereas those features considered to be more adaptive (e.g., authority, self-sufficiency) are unrelated to these types of outcomes (Barry et al, 2003;Washburn et al, 2004).…”
Section: Juvenile Narcissismmentioning
confidence: 92%
“…The few available studies suggest that narcissism is positively correlated with conduct problems and aggression in children (Barry et al, 2003) and adolescents (Costello & Dunaway, 2003;Salmivalli, Kaukiainen, Kaistaniemi & Laerspetz, 1999;Washburn et al, 2004). For example, among school-age children, Barry and colleagues (2003) found an association between narcissism and features of conduct disorder and oppositional defiant disorder that was moderated by the child's level of self-esteem, such that children with high levels of narcissism and low self-esteem showed the highest rates of conduct problems.…”
Section: Juvenile Narcissismmentioning
confidence: 99%
See 3 more Smart Citations